Zakat Saham Dalam Sistem Ekonomi Islam (Kajian Atas Pemikiran Yusuf Qardhawi) - Refky Fielnanda (Al-Tijary, 2017)
This study to explore the thought of Yusuf Qardhawi about zakah on stock. As the purpose of which is to know about the existence of stock in the Islamic economic system according to the perspective of Yusuf Qardhawi and his method to determine the law about the obligatory of zakah on stock. Yusuf Qardhawi said that issuing, owning, buying, selling and transacting the stock is halal and there is no prohibition as long as the activities of the company formed from those stocks do not contain activities prohibited by shari'ah. According to Yusuf Qardhawi's thought that all of the stock types of companies, both industrial companies and trading companies must be obliged to pay zakah based on the announcement of the paragraph about the obligation of zakah ie surah at-Taubah paragraph 103. Then Yusuf Qardhawi expalained if we take an opinion that sees stock according to the type of company, zakah on stock of industrial companies can be analogous to zakah on investment plant, building, etc. which is analogous to zakat on agricultural land, and issued it's zakah amount 10% of net profit. While the trading company is analogous to zakah trading, its issued from the stock in accordance with the prevailing market price plus profit.